MT1‐MMP and ADAM10/17 exhibit a remarkable overlap of shedding properties. (9th August 2022) - Werny, Ludwig; Grogro, Antonia; Bickenbach, Kira; Bülck, Cynthia; Armbrust, Fred; Koudelka, Tomas; Pathak, Kriti; Scharfenberg, Franka; Sammel, Martin; Sheikhouny, Farah; Tholey, Andreas; Linder, Stefan; et al.
Abstract : Membrane‐type‐I matrix metalloproteinase (MT1‐MMP) is one of six human membrane‐bound MMPs and is responsible for extracellular matrix remodelling by degrading several substrates like fibrillar collagens, including types I‐III, or fibronectin. Moreover, MT1‐MMP was described as a key player in cancer progression and it is involved in various inflammatory processes, as well as in the pathogenesis of Alzheimer's disease (AD). The membrane‐tethered metalloprotease meprin β as well as a disintegrin and metalloproteinase 10 (ADAM10) and ADAM17 are also associated with these diseases. Interestingly, meprin β, ADAM10/17 and MT1‐MMP also have a shared substrate pool including the interleukin‐6 receptor and the amyloid precursor protein. We investigated the interaction of these proteases, focusing on a possible connection between MT1‐MMP and meprin β, to elucidate the potential mutual regulations of both enzymes. Herein, we show that besides ADAM10/17, MT1‐MMP is also able to shed meprin β from the plasma membrane, leading to the release of soluble meprin β. Mass spectrometry‐based cleavage site analysis revealed that the cleavage of meprin β by all three proteases occurs between Pro602 and Ser603, N‐terminal of the EGF‐like domain. Furthermore, only inactive human pro‐meprin β is shed by MT1‐MMP, which is again in accordance with the shedding capability observed for ADAM10/17. Vice versa, meprin β also appears to shed MT1‐MMP, indicating a complex regulatory network. Further studies will elucidate this well‐orchestrated proteolytic web under distinct conditions in health and disease and will possibly show whether the loss of one of the above‐mentioned sheddases can be compensated by the other enzymes. Abstract : Besides ADAM10 and ADAM17, we identified human MT1‐MMP as an additional sheddase of human pro‐meprin β. Surprisingly, all observed shedding properties of MT1‐MMP with regard to meprin β appeared to be similar to its shedding by ADAM10/17, including the identical cleavage site between Pro602 and Ser603 as well as the species‐specific differences between man and mouse.